Audiological Findings in Children with PLA2G6-Associated Neurodegeneration - Vandana, Valiyaparambath Purushothaman; Darshini, Jeevendra Kumar; Sankaran, Bindu Parayil (Journal of the American Academy of Audiology, 2022)
Background Audiological manifestations of patients with PLA2G6-associated neurodegeneration are limited.Objective To analyze the audiological findings in a cohort of 13 children with infantile neuroaxonal dystrophy (INAD).Method Patients underwent a battery of audiological tests including tympanometry, distortion product otoacoustic emissions, impedance audiometry, and Brainstem Auditory Evoked Potentials (BAEPs).Results Audiological studies of 13 children indicated sensorineural hearing loss in six children and auditory neuropathy spectrum disorder in four children.Conclusion This study may extend the auditory findings for INAD. Additional studies on quality of life and cognitive-brain degeneration related to this disease are required before making appropriate recommendations for aural rehabilitation.
Keywords: infantile neuroaxonal dystrophy; PLA2G6; sensorineural hearing loss; auditory neuropathy spectrum disorder